TOKSISITAS AKUT BANDOTAN (Ageratum conyzoides ) TERHADAP MORTALITAS KUMBANG JAGUNG (Sitophilus zeamais Motschulsky) - Dian Mutiara Ita Emilia (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2013)
Investigation about Acut  Toxicity of   Bandotan Leaf ( Ageratum conyzoides)  to Mortality Maize Weevil (Sitophilus zeamays) was conducted on Juni – September 2013 in laboratory Biology Faculty of Mathematic  University of PGRI Palembang. Acut tocxicity  test using the maize weveil  bioassay method with a time of 96 hours aplication. The shows that results that leaf of Bandotan were toxic to maize weevil whith  24 hours, 48 hours and  96 hours LC 50 were   29.279 %, 21.610 %  and   16.477  %. Key words ;   Toxicity. Ageratum conyzoides,   Sitophilus zeamais M.).   LC50